Arisan Online Buku Edukasi Anak dalam Perspektif Ekonomi Syariah - Sukmawardaya, Alfirsyah; Azizurrahman; Tjahjadi, Tony; Sujianto, Agus Eko (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study examines the phenomenon of online exchange meetings for children's counseling books from the perspective of Sharia economics. This study uses a qualitative approach to problem study to investigate the application of Sharia economics in the context of social gatherings, member motivations, and impacts. Information was collected and analyzed inductively through in-depth interviews, participant observation, and document analysis.  The research results show that this online social gathering successfully implemented the economic principles of Sharia, especially in the aspects of profit sharing and transparency.  Our members' participation is motivated by providing valuable instruction to children in line with Islamic values. Online collections of children's novels have a positive impact on children's literacy and society, becoming a comprehensive economic model that combines social, economic and educational aspects.